Profile of Critical Thinking Skills of Chemistry Education Students in Solving Problems Related to the Concept of Mole - Jenny Pratiwi; Rahmat Rasmawan*; Erlina Erlina; Eny Enawaty; Maria Ulfah (Jurnal Pendidikan Sains Indonesia, 2023)
Critical thinking skills are needed in solving problems because identitying problems requires an analytical thinking process based on clear data and reasons. The purpose of this study was to describe the critical thinking skills of chemistry education students class of 2020 in solving problems related to the mole concept. The type of research used in this study is descriptive quantitative. Subjects who participated voluntarily in this study were 38 people out of 49 chemistry education students class of 2020. Data collection techniques using measurement and direct communication. The research instrument used was adopted from the stoichiometry e-book developed by Rahmat Rasmawan in 2022 which has been validated by 10 validators with a score of 85 which means it is valid and can be used. The data analysis technique used was descriptive analysis. The results showed that critical thinking skills in the skilled category was 40%, while in the less and unskilled were 55% and 5% respectively. In each indicator, which are making assumptions is in the highly skilled criteria with 66%, making inductive thinking conclusions are in the skilled criteria with 84%, and interpreting information is in the unskilled criteria with 61%. The critical thinking skills of students in the 2020 chemistry education class are still in the unskilled category, this is due to the inhibiting factors, namely the online learning system and inappropriate learning methods